Evaluation of Hydrophilized Graphite Felt for Electrochemical Heavy Metals Detection (Pb2+, Hg2+) - Laila Bouabdalaoui; Benjamin Le Ouay; Thibaud Coradin; Christel Laberty-Robert (International Journal of Electrochemistry)
Hydrophilized graphite felt has been used, for the first time, for the electrochemical detection of Hg2+ ions both as single metal species and via its simultaneous detection with Pb2+. To do so, square wave voltammetry (SWV) method was developed with alginate modified graphite felt as working electrode. The structure of the graphite felt such as its high porosity and specific surface area coupled with its good electrical conductivity allows achieving large peak currents via the SWV method, suggesting that the alginate coating helps to preconcentrate metals at the carbon surface. The as-described electrode has low cost, it is easy to manipulate, and the electrochemical analysis can be performed by simple immersion of the felt in the metal solution.